Analisis Jurnal Internasional Pengaruh Komunikasi Kerja pada Kinerja Karyawan Perusahaan - Samsudin, Acep; Prabowo, Budi; Susanti, Bene Dicta Ary; Zahrah, Alya Nadia; Maharanie, Putri (Ikatan Da'i Indonesia, 2024)
Analyzing several journals was carried out to find out what influence work communication has on the performance of workers in the company. To find out and gain a clearer understanding of how factors might influence the effectiveness of communication in organizations or companies. The method used is data analysis by paying attention to things such as the influence of work motivation, work compliance, work communication and employee performance. Looking at the existing data, it can be concluded that work motivation and communication in a company can increase employee productivity. Good work communication can be useful for companies in helping develop good work communication strategies and effectiveness.